Kedudukan Suntik Mati Terhadap Terpidana Mati Dari Perspektif Hak Asasi Manusia - Rafliansyah Manti; Lisnawaty W. Badu; Jufryanto Puluhulawa (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The aim of this research is to legally analyze the procedures for implementing the death penalty in Indonesia from a human rights perspective. Apart from that, it discusses the type of execution of the death penalty by injection by considering the method of carrying out the death penalty against the perception of justice and humanity. The type of research used by researchers in preparing this research based on the phenomenon being studied is juridical research or normative legal research. The method used uses 2 types of approaches, namely using a statutory approach or what can be called a Statue Approach and a Conceptual Approach.The results of the research show that the existence of the death penalty, which is a very frightening type of crime, raises pros and cons in society, so that the electability of the death penalty is debated to this day. However, it is not only about the existence of the death penalty but the implementation/method used in the execution of death row convicts, carried out by being shot to death, is regulated in Law No/2 Presidential Decree of 1964 concerning procedures for carrying out the death penalty which is considered to be torturous and it looks very cruel, in contrast to countries that have implemented executions using lethal injection which is considered an easier method. This is based on the purpose of euthanasia (lethal injection), namely a way to end a person's life in a peaceful and painless way.